Pengembangan Modul Pembelajaran Ragam Hias Bagi Siswa Kelas VII SMP Negeri 1 V Koto Timur - Erdi Syawal; Efrizal Efrizal (Universitas Negeri Padang, 2023)
This observation aims to create a valid and practical decorative variety learning module product. In this development, 4-D model is the research model used in this development. 4-D model is divided into definition, design, development, dissemination. To fit the short time, the implementation of research is limited to the development stage. This was fixed on input from expert validators, including 3 lecturers of fine arts, 1 lecturer of language and teacher of cultural arts. The development of the decorative learning module was carried out with a small-stage test conducted by 15 grade VII students of SMP Negeri 1 V Koto Timur Padang Pariaman Regency. On the validation sheet given to the validator, the results obtained, namely 87,12% categorized as very valid. While the influence of practical test addressed to students, results of the practicality test given to students, the results were 91,6% categorized as very practical. Based on the assesments of the validater experts and students regarding the decorative learning module it is valid and practical. Keyword: Learning Module, Decorative